2017
DOI: 10.1007/978-3-319-56246-9_18
|View full text |Cite
|
Sign up to set email alerts
|

MiR-140-3p Downregulation in Association with PDL-1 Overexpression in Many Cancers: A Review from the Literature Using Predictive Bioinformatics Tools

Abstract: Programmed death-ligand 1 (PD-L1) has been speculated to play a critical role in suppression of the immune system and it can be upregulated in cancer cells, which may allow cancers to evade the host immune system. MicroRNAs (miRNAs) are small non-coding RNA molecules (containing about 22 nucleotides), that function in RNA silencing and post-transcriptional regulation of gene expression. MiRNAs were found deregulated (upregulated or downregulated) and implicated in cancer development with various roles which de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…In addition, previous experiments demonstrated that decreased expression of ZO-1, occludin, and claudin-5 increased BTB permeability 31 . Our study demonstrated that the expression of miR-140-3p was suppressed in GECs, and some literature reported that miR-140-3p was downregulated in many tissue cancers 12 , and its expression in lung cancer cells was lower than that in normal lung epithelial cells 32 , which was consistent with our results. In addition to regulating the expression of genes related to the nervous system, miR-140-3p can also regulate the other target genes expression 33 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, previous experiments demonstrated that decreased expression of ZO-1, occludin, and claudin-5 increased BTB permeability 31 . Our study demonstrated that the expression of miR-140-3p was suppressed in GECs, and some literature reported that miR-140-3p was downregulated in many tissue cancers 12 , and its expression in lung cancer cells was lower than that in normal lung epithelial cells 32 , which was consistent with our results. In addition to regulating the expression of genes related to the nervous system, miR-140-3p can also regulate the other target genes expression 33 .…”
Section: Discussionsupporting
confidence: 92%
“…MicroRNAs (miRNAs) are noncoding, single-stranded, small RNA molecules with 18–25 nucleotides in length that can inhibit gene expression at the post-transcriptional level through nucleotide base pairings between complementary seed sequences of miRNAs and the target gene 3′untranslated regions (3′-UTR) 12 . Some miRNAs are considered to be proto-oncogenes and tumor suppressor genes, which are used as novel and promising therapeutic targets for cancer treatment by negatively regulating transcription or translation of target gene 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…evidence has indicated that mirnas regulate Pd-l1 expression in cancer (36). For example, downregulation of mir-140-3p is closely associated with overexpression of Pdl-1 in many cancers, including breast and lung cancer (37). in malignant pleural mesothelioma, tumor suppressor gene mirnas (mir-15b, mir-16, mir-193a-3p, mir-195, and mir-200c) downregulate the expression of Pd-l1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that miR-140 levels are negatively correlated with PD-L1 expression, while PD-L1 expression is positively correlated with cyclin E expression [21, 22]. We therefore hypothesized a relationship between miR-140, PD-L1, and cyclin E. To investigate their roles in expression of cyclin E, the expression of miR-140 and PD-L1were manipulated.…”
Section: Resultsmentioning
confidence: 99%